Interspecific Aggression and Food Competition between the Global Invader Palaemon macrodactylus and the Native Palaemon elegans - Francesco Cavraro; Chiara Facca; Luca Altavilla; Stefano Malavasi (Journal of Marine Science and Engineering, 2022)
The impact of invasive alien species on native communities can act at different levels both by affecting the ecosystem’s structure (i.e., mainly in the case of vegetation) and through direct interactions (i.e., competition for food or space). Behavioral studies under controlled conditions can provide relevant information on both the invasive potential of alien species and the potential impact of the invaders on the local native species. In the laboratory, the competition for food resources between the invasive oriental shrimp Palaemon macrodactylus, Rathbun, 1902, and the Mediterranean native shrimp Palaemon elegans, Rathke, 1836, was analyzed. These species are typical residents of coastal transitional and estuarine waters, so the experiments were carried out using two salinity conditions that characterize the coastal lagoon of Venice. Although at both salinity treatments the alien species tended to be more aggressive than the native one, significant differences between the two species were mainly observed at a salinity of 30. In particular, at a salinity of 30, P. macrodactylus spent more time attending to the food source than the native species. The results are discussed in light of the potential inter-specific competition between the two species within the conditions of the Venice lagoon.